Teaching Pedestrian untuk Anak Sekolah Dasar di Ruang Pedestrian Menuju ke Sekolah SD Pedalangan, Banyumanik - Anita Ratnasari Rakhmatulloh; Diah Intan Kusumo Dewi (Jurnal Planologi, 2020)
Walking activities are currently eroded due to the increasingly dominant use of motorized modes. The high use of motorized vehicles is often dangerous for children. Pedalangan Elementary School located in Banyumanik District is an area affected by increased activity due to the stipulation of the Tembalang District as an Education Area. The high movement or volume of traffic in the corridor is not balanced with adequate road width. It will increase the risk of accidents for elementary school students. The purpose of this study is to provide education to students of Pedalangan Elementary School about the ethics of walking on pedestrian paths, crossing roads and manners in open spaces (parks) which are expected to influence the improvement of students' habits to walk to school or public spaces. This study uses qualitative methods with data collection methods in the form of observation. The results of this study are students' understanding of the ethics of walking on pedestrian paths, crossing and manners in the park increased after education about road safety.